Steady-State Drainage of an Aqueous Foam - WEAIRE, DENIS LAWRENCE; HUTZLER, STEFAN (American Physical Society, 1993)
The process of wetting of a monodisperse foam by the continuous addition of liquid from the top has been investigated for a cylindrical column. The velocity of the interface between dry and wet foam was found to vary as the square root of the rate of addition of liquid. Evidence of a structural transformation was found around gas fraction ?=0.87. It was interpreted as arising from the collapse of the four-sided faces of the (Kelvin) polyhedra which constitute the foam cells, and this was directly observed when large bubbles were used. There is a second transition at around ?=0.6, with the onset of bubble motion.
PUBLISHED
Keywords: Physics